1952
DOI: 10.1017/s0025315400052942
|View full text |Cite
|
Sign up to set email alerts
|

A photographic survey of certain areas of sea floor near Plymouth

Abstract: An improved underwater photographic apparatus has been used to take further series of photographs of the sea bottom near Plymouth. The photographs in the present series are each ¼ m.2 in area instead of 1 m.2, and at this scale definition is much better.Photographs of the bottom in the Rame Mud area showed ripple marks but no living epifaunal animals. In an area south of the Rame Mud, on a muddy sand and gravel bottom and in a similar area 6 miles south of Looe, dense populations of the brittle-star, Ophiothri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1955
1955
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 2 publications
1
47
0
Order By: Relevance
“…Yet living (as they commonly do) on a fairly bare substratum, they form aggregations unless, apparently, the density is too low. Such aggregations on the sea bed have been photographed by Vevers (1951Vevers ( , 1952. The main physical differences between the two bays are: (1) Kames Bay is more sheltered and has a finer deposit of sand or mud at each station with fewer stones and shells than White Bay; (2) in Kames Bay, a substantial quantity of vegetable debris is washed backwards and forwards with the tide in the upper part of the sublittoral zone and there is a large amount of decomposing organic material mixed with the superficial mud at a depth of about 3°m; both these circumstances are practically absent in White Bay.…”
Section: Crustacea:the Writers See Nothing To Add To What the Tables mentioning
confidence: 99%
“…Yet living (as they commonly do) on a fairly bare substratum, they form aggregations unless, apparently, the density is too low. Such aggregations on the sea bed have been photographed by Vevers (1951Vevers ( , 1952. The main physical differences between the two bays are: (1) Kames Bay is more sheltered and has a finer deposit of sand or mud at each station with fewer stones and shells than White Bay; (2) in Kames Bay, a substantial quantity of vegetable debris is washed backwards and forwards with the tide in the upper part of the sublittoral zone and there is a large amount of decomposing organic material mixed with the superficial mud at a depth of about 3°m; both these circumstances are practically absent in White Bay.…”
Section: Crustacea:the Writers See Nothing To Add To What the Tables mentioning
confidence: 99%
“…It forms dense beds on all coasts of the English Channel, mainly on coarse sediments subject to high tidal currents (Vevers 1952, Cabioch 1968, Cabioch & Glacon 1975, 1977, and also on muddy gravels bottoms (Warner 1971). These dense aggregations of this passive suspension-feeder, feeding mainly on phytoplankton (Warner & Woodley 1975), are assumed to have a significant effect on the exchanges of organic matter at the water-sediment interface (Hily 1991, Davoult et al 1998).…”
mentioning
confidence: 99%
“…Although our results suggested no advantages to A. filiformis when in dense aggregations, there were also presumably no disadvantages. Vevers (1952) suggested that densely populated patches of the brittle star Ophiothrix fragilis occurred within the Plymouth region as a result of a consistent reliable food source supplied by tidal streams. Therefore, while aggregation benefits, in terms of lowering energetic costs to the organism, may not occur, there are other factors such as food supply which could possibly control distribution patterns for certain populations in their natural habitats.…”
Section: Effects Of Densitymentioning
confidence: 99%